UTILIZATION OF LOCAL RESOURCES IN UZBEK NATIONAL PRESS DURING THE SECOND WORLD WAR (Scientific journal of the Fergana State University, 2023)
This article analyzes the history of the use of local and domestic resources in Uzbekistan during the Second World War to strengthen the country's defense capabilities and meet the needs of the population in chronological order, based on data from the Uzbek national press.The study also found that wild fruits, plants, fruit seeds and melon seeds, which had not been used before, were used to increase food resources in Uzbekistan during the war years. In particular, the shells of the consumed fruits have been replaced by industrial wastes, which have been in short supply due to the war. The skin of a single pomegranate is used as an important raw material in tanning (leather processing), ink making, and medicine.